2009
DOI: 10.1111/igc.0b013e3181a832a2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hybrid Capture II Assay With the Human Papillomavirus DNA Chip Test for the Detection of High-Grade Cervical Lesions

Abstract: Cervical intraepithelial neoplasia (CIN) 2 is used as the threshold for treatment decisions. This study was conducted to evaluate the clinical efficacy of the Hybrid Capture II assay (HC2) and the human papillomavirus (HPV) DNA chip test (HDC) for detecting HPV in high-grade cervical lesions CIN2 or greater, including adenocarcinoma (CIN2+). Seven hundred forty-one women with abnormal cervical cytology were evaluated with the HC2, the HDC, and histological assessment of the cervix. The overall agreement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
4
24
0
Order By: Relevance
“…Our findings are consistent with most previous studies showing similar negative HPV testing rates in invasive cervical cancer. 5,[10][11][12] In our study, HPV À rates in patients with invasive cervical cancer seemed to increase with increased time before cancer diagnosis, and it is reasonable to attribute that trend to the smaller size of the lesion or the lower viral titers during earlier periods.…”
Section: Commentmentioning
confidence: 47%
See 2 more Smart Citations
“…Our findings are consistent with most previous studies showing similar negative HPV testing rates in invasive cervical cancer. 5,[10][11][12] In our study, HPV À rates in patients with invasive cervical cancer seemed to increase with increased time before cancer diagnosis, and it is reasonable to attribute that trend to the smaller size of the lesion or the lower viral titers during earlier periods.…”
Section: Commentmentioning
confidence: 47%
“…HC2 was the first FDA-approved HPV test, and studies from different countries, including the United Kingdom, Slovenia, China, and Korea, have demonstrated that HC2 is associated with negative results in cervical cytology specimens from patients with cervical cancer; HC2 À rates have varied from 5.0% to 25%. [14][15][16][17][18] The question is, whether those are true-negative or false-negative results. In a recent study, 3 of 31 patients 10 (9.7%) diagnosed with invasive cervical squamous cell carcinoma and tested within the prior 12 months for hrHPV by HC2 had negative HC2 results.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate is actually probably slightly higher when the HPV test is performed not on the whole vial but on the cell-enriched fraction (128). Data from studies performed in several different countries using different molecular tests as comparators indicate that the HC2 test has a false-negative rate of about 5 to 12% in patients with cervical cancer (131,(138)(139)(140)(141)(142)(143)(144). Since the HC2 test does not contain an internal control, it is not possible to determine the adequacy of the specimen or the presence of potentially interfering substances.…”
Section: Dna-based Tests: Signal Amplificationmentioning
confidence: 99%
“…13 Even though HPV infection is widely implicated in the pathogenesis of cervical cancer, only 91% of cervical carcinomas tested at the time of diagnosis were positive for hr-HPV. 14,15 The reasons for this are unclear, but Sundstrom et al 16 hypothesize that HPV 16 viral load may decrease in a significant subset of patients developing cervical carcinoma. In fact, even though viral infection may be present in the preceding years, it may be below the threshold detectable by current clinical testing.…”
Section: Resultsmentioning
confidence: 99%